Collective Memory and the Transformations of Political Myth in the Era of the Mass Media (Acta Scientiarum. Human and Social Sciences, 2022)
If myths have been narrated since time immemorial, this study argues that a novel kind of political myth has emerged over the past decades that has been adapted to a specifically modern significance and function. To account for the appearance of this novel form of political myth, I investigate the role of the mass media. In this perspective, the development and technological advance of the mass media has brought about a transformation in the modes of public experience and remembrance and a corresponding metamorphosis in the specific character of public space that lends to contemporary political myth its unique significance and function